2018
DOI: 10.7554/elife.38497
|View full text |Cite
|
Sign up to set email alerts
|

A liquid-like organelle at the root of motile ciliopathy

Abstract: Motile ciliopathies are characterized by specific defects in cilia beating that result in chronic airway disease, subfertility, ectopic pregnancy, and hydrocephalus. While many patients harbor mutations in the dynein motors that drive cilia beating, the disease also results from mutations in so-called dynein axonemal assembly factors (DNAAFs) that act in the cytoplasm. The mechanisms of DNAAF action remain poorly defined. Here, we show that DNAAFs concentrate together with axonemal dyneins and chaperones into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(88 citation statements)
references
References 62 publications
(108 reference statements)
6
68
1
Order By: Relevance
“…Capped cfap44 mRNA was synthesized using mMESSAGE mMACHINE SP6 transcription kit (ThermoFisher Scientific). Each 90 pg of GFP-cfap44 and mCherry-Dnaaf2/Ktu mRNAs were injected into two ventral blastomeres and live-imaging was performed as previously described (in Huizar et al, 2018). For RNA staining, embryos were fixed with Dent's fixative (20% DMSO and 80% methanol) at stage 23 and were stained by 500 nM of SYTO RNAselect Green Fluorescent Cell Stain (Invitrogen) for 20min and were imaged after washing.…”
Section: Protein Structure Modellingmentioning
confidence: 99%
See 2 more Smart Citations
“…Capped cfap44 mRNA was synthesized using mMESSAGE mMACHINE SP6 transcription kit (ThermoFisher Scientific). Each 90 pg of GFP-cfap44 and mCherry-Dnaaf2/Ktu mRNAs were injected into two ventral blastomeres and live-imaging was performed as previously described (in Huizar et al, 2018). For RNA staining, embryos were fixed with Dent's fixative (20% DMSO and 80% methanol) at stage 23 and were stained by 500 nM of SYTO RNAselect Green Fluorescent Cell Stain (Invitrogen) for 20min and were imaged after washing.…”
Section: Protein Structure Modellingmentioning
confidence: 99%
“…At the same time, RNA-associated proteins have also emerged as critical factors for the assembly of liquid-like organelles, including not only ubiquitous organelles such as nuceloli and stress granules, but also cell-type specific organelles such as Cajal bodies (Banani et al, 2017;Lin et al, 2015;Mittag and Parker, 2018;Sawyer et al, 2016). In a recent study, we described novel liquid-like organelles called DynAPs that are specific to multiciliated cells, where they control the assembly of dynein motors that drive ciliary beating (Huizar et al, 2018). DynAPs are present in motile ciliated cells of Xenopus, zebrafish, and mammals, and their disruption is associated with human motile ciliopathy Huizar et al, 2018;Li et al, 2017; Here, we demonstrate the feasibility of determining the RNA-interacting proteome of a defined vertebrate embryonic tissue using DIF-FRAC, a systematic and universal (i.e., label-free) method (Mallam et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SPAG1, like other proteins with TPR domains, (Table 1) mediates the delivery of clients from Hsp70 to Hsp90, thanks to simultaneous anchoring of the chaperones via EEVD residues within Hsp70 and Hsp90 C-terminal end to the designed TPR domains of SPAG1 [64]. SPAG1, besides RuvBL1, RuvBL2, and PIH1D2, interacts (possibly indirectly) with DNAAF5/HEATR2 (HEAT Repeat-Containing) and DNAAF2 (Table 1), and co-localizes with them in DynAPs [27,65]. Recent studies on ciliogenesis in human primary airway epithelial cells have shown that DNAAF5, SPAG1, and DNAAF2 undergo transcription during the early stages of airway epithelial cell differentiation.…”
Section: Composition Of R2sp Complex and Function In Dynein Arm Preasmentioning
confidence: 99%
“…Mature ciliated cells exhibited 42 genes uniquely upregulated in heavy smokers which included the TF, XBP1, and genes involved in ER processing and unfolded protein and heat shock responses ( Figure 4f). As heat shock family chaperonins were recently shown to be required for axonemal protein complex assembly 71 , prolonged smoking may enhance the ciliated cell-specific protein-folding program to counteract smokingrelated protein damage and misfolding.…”
Section: Sequential Transcriptional Programs Drive Motile Ciliogenesismentioning
confidence: 99%